2008
DOI: 10.1007/s11695-008-9627-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Bypass is not Associated with Protein Malnutrition in Morbidly Obese Patients

Abstract: Malnutrition is difficult to diagnose in obese patients undergoing surgery. The large weight loss is most often not associated with protein malnutrition. Whether gastric bypass induces protein malnutrition remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…As shown by others [18,19], in our cohort albumin and prealbumin levels decreased after bariatric surgery compared to the presurgical period. No individual in our cohort presented with a plasma albumin level <35 g/L.…”
Section: Discussionsupporting
confidence: 83%
“…As shown by others [18,19], in our cohort albumin and prealbumin levels decreased after bariatric surgery compared to the presurgical period. No individual in our cohort presented with a plasma albumin level <35 g/L.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, these protein deficiencies were always mild. In protein-deficient patients the mean albumin level was 36.5 (36-37) g/l after LSG and 33 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) g/l after LRYGB. Ritz et al observed that plasma concentration of albumin decreased after gastric bypass but returned to initial values after 12 months [32].…”
Section: Discussionmentioning
confidence: 96%
“…Postoperative patients often have inadequate protein intake due to food intolerances and decreased caloric intake [10,24,25]. However, when only blood proteins are considered, the majority of patients do not appear to be malnourished [25,26]. Blood proteins are less sensitive indicators of nutritional status than physical examination that includes an assessment of muscle mass [27].…”
Section: Proteins and Nutritional Statusmentioning
confidence: 99%